Thymic dendritic cell subsets display distinct efficiencies and mechanisms of intercellular MHC transfer - Kroger, Charles J. (J Immunol, 2016)
Thymic dendritic cells (DC) delete self-Ag-specific thymocytes, and drive development of FoxP3-expressing immunoregulatory T cells. Unlike medullary thymic epithelial cells (mTEC), which express and present peripheral self-Ag, DC must acquire self-Ag to mediate thymic negative selection. One such mechanism entails the transfer of surface MHC-self peptide complexes from mTEC to thymic DC. Despite the importance of thymic DC “cross-dressing” in negative selection, the factors that regulate the process, and the capacity of different thymic DC subsets to acquire MHC and stimulate thymocytes are poorly understood. Here intercellular MHC transfer by thymic DC subsets was studied using a MHC-mismatch-based in vitro system. Thymic conventional DC (cDC) subsets SIRPα(+) and CD8α(+) readily acquired MHC class I and II from TEC but plasmacytoid DC (pDC) were less efficient. Intercellular MHC transfer was donor cell-specific; thymic DC readily acquired MHC from TEC plus thymic or splenic DC, whereas thymic or splenic B cells were poor donors. Furthermore DC origin influenced cross-dressing; thymic versus splenic DC exhibited an increased capacity to capture TEC-derived MHC, which correlated with direct expression of EpCAM by DC. Despite similar capacities to acquire MHC-peptide complexes, thymic CD8α(+) cDC elicited increased T cell stimulation relative to SIRPα(+) cDC. DC cross-dressing was cell-contact dependent and unaffected by lipid raft disruption of donor TEC. Furthermore, blocking PI3K signaling reduced MHC acquisition by thymic CD8α(+) cDC and pDC but not SIRPα(+) cDC. These findings demonstrate that multiple parameters influence the efficiency of and distinct mechanisms drive intercellular MHC transfer by thymic DC subsets.